Primary Angioplasty A Practical Guide (Springer Singapore, 2018)
This book is open access under a CC BY 4.0 license. This quick-reference handbook offers a concise and practical review of key aspects of the treatment of ST-segment elevation myocardial infarction (STEMI) in the era of primary percutaneous coronary intervention (PPCI). In the context of STEMI, PPCI is the preferred mode of emergency revascularization. Access to PPCI is rapidly increasing and is now routinely practiced in both general and specialist hospitals and there has been a recent emphasis on developing STEMI networks to enhance and expedite the referral pathway. This coupled with concurrent developments to enhance the safety and efficacy of the PPCI procedure has heralded an era where STEMI interventions are increasingly considered an important subspecialty within interventional cardiology. Written by leading cardiologists who have been instrumental in the adoption of PPCI in their respective institutions, the book provides junior and senior cardiologists alike with insightful and thought-provoking tips and tricks to enhance the success of PPCI procedures, which may in turn translate into direct improvements in outcomes. The book is also relevant for healthcare providers and emergency department physicians.